The effect of diaphragm muscle exercise on dynamic balance amomg post-covid-19 older adults in Klang Valley, Malaysia - Goh, Le Yi (2024)
Background: The COVID-19 pandemic has disproportionately affected older adults, leading to long-term complications, including diaphragm dysfunction, which may contribute to impaired dynamic balance and increased fall risk. Despite the known impact of diaphragm muscle weakness on respiratory function, its effect on balance in post-COVID-19 older adults has not been thoroughly investigated.